Turkish Adaptation of the Mentorship Effectiveness Scale: A validity and Reliability Study - Yirci, Ramazan; Karakose, Turgut; Uygun, Harun; Ozdemir, Tuncay Yavuz (Modestum Ltd, 2016)
The purpose of this study is to adapt the Mentoring Relationship Effectiveness Scale to Turkish, and to conduct validity and reliability tests regarding the scale. The study group consisted of 156 university science students receiving graduate education. Construct validity and factor structure of the scale was analyzed first through exploratory factor analysis, then with confirmatory factor analysis. One item was deleted from the scale after the exploratory factor analysis and the scale was observed in its original one dimensional form. The confirmatory factor analysis indicated that the one dimensional model of the scale was acceptable. Reliability of the scale was examined with test-retest and internal consistency (Cronbach Alpha) methods. The internal consistency coefficient for the whole scale was 0.936. The reliability coefficient for the test-retest, which was carried out two weeks apart, was 0.89. The findings suggest that Mentoring Relationship Effectiveness Scale is sufficiently reliable and valid for science education of graduate students.
Keywords: mentorship; graduate student; science education; validity; reliability